MRSA COLONITATION DETECTION IN OBJECT NEAR PATIENTS IN BURN UNIT RSUD DR. SOETOMO - INDONESIA - Wahyunitisari, Manik Retno; Mustikasari, Melisa Indah; Hariani, Lynda (Journal of Vocational Health Studies, 2021)
Background: Burn unit is a unit where patients with a burn wound in which the patient's skin is not intact are taken care of. Methicillin-resistant Staphylococcus aureus (MRSA) as the prototype of a nosocomial pathogen is usually transmitted through contact from the surfaces of the object to the non-intact skin. Therefore, the possibility of MRSA infection increase in the burn unit. Purpose: The purpose of this research is to find out whether there is any colonization of MRSA on the objects around burn unit patients that can contribute to the spreading of MRSA in the RSUD Dr.Soetomo Indonesia. Method: The sampling period was started from October 2019 until March 2020. Samples were taken randomly from 28 patients in the Burn unit RSUD Dr.Soetomo -ndonesia and then tested for identification in the microbiology laboratory of the medical faculty, Universitas Airlangga. Result: Nineteen bacterial growths were obtained from twenty-eight samples taken, nine of them were confirmed as Stahylococcus aureus and one from nine of them was confirmed as MRSA. Conclusion: MRSA contamination was found on an object around the patient burn unit Dr. Soetomo-Indonesia which comes from the stethoscope membrane.